Effects of aging on otolith morphology and functions in mice - Ueda, Keita; Imai, Takao; Ito, Taeko; Okayasu, Tadao; Harada, Shotaro; Kamakura, Takefumi; Ono, Kazuya; Katsuno, Tatsuya; Tanaka, Tatsuhide; Tatsumi, Kouko; Hibino, Hiroshi; Wanaka, Akio; et al. (Frontiers in Neuroscience, 2024)
BackgroundIncreased fall risk caused by vestibular system impairment is a significant problem associated with aging. A vestibule is composed of linear acceleration-sensing otoliths and rotation-sensing semicircular canals. Otoliths, composed of utricle and saccule, detect linear accelerations. Otolithic organs partially play a role in falls due to aging. Aging possibly changes the morphology and functions of otoliths. However, the specific associations between aging and otolith changes remain unknown. Therefore, this study aimed to clarify these associations in mice.MethodsYoung C56BL/6 N (8 week old) and old (108–117 weeks old) mice were used in a micro-computed tomography (μCT) experiment for morphological analysis and a linear acceleration experiment for functional analysis. Young C56BL/6 N (8 week old) and middle-aged (50 week old) mice were used in electron microscopy experiments for morphological analysis.ResultsμCT revealed no significant differences in the otolith volume (p = 0.11) but significant differences in the otolith density (p = 0.001) between young and old mice. μCT and electron microscopy revealed significant differences in the structure of striola at the center of the otolith (μCT; p = 0.029, electron microscopy; p = 0.017). Significant differences were also observed in the amplitude of the eye movement during the vestibulo-ocular reflex induced by linear acceleration (maximum amplitude of stimulation = 1.3G [p = 0.014]; maximum amplitude of stimulation = 0.7G [p = 0.015]), indicating that the otolith function was worse in old mice than in young mice.DiscussionThis study demonstrated the decline in otolith function with age caused by age-related morphological changes. Specifically, when otolith density decreased, inertial force acting on the hair cells decreased, and when the structure of striola collapsed, the function of cross-striolar inhibition decreased, thereby causing a decline in the overall otolith function.